Renal involvement in sarcoidosis: histological patterns and prognosis, an Italian survey.: Renal involvement in sarcoidosis. - Rastelli, Francesco; Baragetti, Ivano; Buzzi, Laura; Ferrario, Francesca; Benozzi, Luisa; Di Nardo, Francesco; Devoti, Elisabetta; Cancarini, Giovanni; Mezzina, Nicoletta; Napodano, Pietro; Gallieni, Maurizio; Santoro, Domenico; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Granulomatous interstitial nephritis in sarcoidosis (sGIN) is generally clinically silent, but in <1% causes acute kidney injury (AKI). Methods: This Italian multicentric retrospective study included 39 sarcoidosis-patients with renal involvement at renal biopsy: 31 sGIN-AKI, 5 with other patterns (No-sGIN-AKI), 3 with nephrotic proteinuria. We investigate the predictive value of clinical features, laboratory, radiological parameters and histological patterns regarding steroid response. Primary endpoint: incident chronic kidney disease (CKD) beyond the 1°follow-up (FU) year; secondary endpoint: response at 1°line steroid therapy; combined endpoint: the association of initial steroid response and outcome at the end of FU. Results: Complete recovery in all 5 No-sGIN-AKI-patients, only in 45% (13/29) sGIN-AKI-patients (p=0.046) (one lost in follow-up, for another not available renal function after steroids). Nobody had not response. Primary endpoint of 22 sGIN-AKI subjects: 65% (13/20) starting with normal renal function developed CKD (2/22 had basal CKD; median FU 77 months, 15–300). Combined endpoint: 29% (6/21) had complete recovery and final normal renal function (one with renal relapse), 48% (10/21) had partial recovery and final CKD (3 with renal relapse, of whom one with basal CKD) (p=0.024). Acute onset and hypercalcaemia were associated to milder AKI and better recovery than subacute onset and patients without hypercalcaemia, women had better endpoints than men. Giant cells, severe interstitial infiltrate and interstitial fibrosis seemed negative predictors in terms of endpoints. Conclusions: sGIN-AKI-patients with no complete recovery at 1°line steroid should be treated with other immunosuppressive to avoid CKD, in particular if males with subacute onset and III stage-not hypercalcaemic AKI.